2019
DOI: 10.1111/sji.12773
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin alleviates interleukin‐1β‐induced inflammatory responses in chondrocytes from osteoarthritis patients: Involvement of HIF‐1α pathway

Abstract: It has been reported that vitexin has anti‐inflammatory effects in osteoarthritis (OA) rats. However, the effects of vitexin on interleukins‐1β (IL‐1β)‐stimulated OA patient‐derived chondrocytes have not been reported. The purpose of this study was to investigate the anti‐inflammatory effects of vitexin on IL‐1β‐stimulated human osteoarthritis chondrocytes and to reveal the involvement of hypoxia‐inducible factor 1α (HIF‐1α) pathway. Enzyme‐linked immunosorbent assay, quantitative real‐time PCR and Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Vitexin, a flavone C-glycoside (5,7,4-trihydroxyflavone-8-glucoside) found in medicinal and other plants, presents anti-inflammatory activities by preventing the oxidative stress, inhibiting pro-inflammatory cytokines production, and increasing the anti-inflammatory cytokine IL-10 [38]. Vitexin inhibited the production of TNF-α, IL-6, nitric oxide (NO), and PGE 2 in human osteoarthritis chondrocytes [110]. Furthermore, vitexin prevents mast cells degranulation [111], reduces the production of pro-inflammatory mediators by neutrophils [112,113] and macrophages [113].…”
Section: Flavonesmentioning
confidence: 99%
“…Vitexin, a flavone C-glycoside (5,7,4-trihydroxyflavone-8-glucoside) found in medicinal and other plants, presents anti-inflammatory activities by preventing the oxidative stress, inhibiting pro-inflammatory cytokines production, and increasing the anti-inflammatory cytokine IL-10 [38]. Vitexin inhibited the production of TNF-α, IL-6, nitric oxide (NO), and PGE 2 in human osteoarthritis chondrocytes [110]. Furthermore, vitexin prevents mast cells degranulation [111], reduces the production of pro-inflammatory mediators by neutrophils [112,113] and macrophages [113].…”
Section: Flavonesmentioning
confidence: 99%
“…In both in vivo and in vitro models, vitexin and 2″-O-α-L-rhamnopyranosyl vitexin treatment suppressed the secretion of activator-inflammatory cytokines TNF, IL-6, and IL-1β proteins' content compared with controls [5,55,97,[100][101][102][103]. Yang et al [104] suggested that the vitexin inhibitory effect on IL-1β-induced inflammatory responses and may be attributed partly to the inhibition of the HIF-1α pathway. In the inflammation model, vitexin exhibited pronounced activity in blocking the expression of TNF-α and the subsequent neutrophil activation [74,105,106].…”
Section: Il-1β Nf-κb and Jun N-terminal Kinase (Jnk)mentioning
confidence: 99%
“…At present, there are reported clinical cases of applying MMPS inhibitors in treating OA [ 24 , 25 ], the underlying mechanism of which is to inhibit the inflammation of articular cartilage and the degradation of cartilage by reducing the production of MMPS, thereby inhibiting inflammation and degradation of articular cartilage. Hence, achieving better protection of chondrocytes, improved outcome of clinical symptoms; helping with the ease and repair of inflammation.…”
Section: Discussionmentioning
confidence: 99%